Study of Congenital Malformation in a Tertiary Care Teaching Hospital - Sahoo, Swaranjika; Ganguly, Ria; Dash , Mrutunjay; Pradhan, Antaryami; Priya, Thambi Gayathri; Mohanty , Mamata Devi (Siriraj Medical Journal, 2021)
Objective: Congenital anomaly is one of the most important causes & being the 5th most common cause of neonatal mortality & morbidity. It may present as a structural or functional abnormality. These defects occur due to defective embryogenesis. Associated factors may be maternal age, maternal TORCH infection, drugs, genetic factors. Antenatal USG reduces the incidence. Materials and Methods: A cross-sectional study was done in the Pediatric department over 1 year. Diagnosis of all congenital anomalies was done by the concerned pediatrician& pediatric surgeon. Data was collected in the specified format. Results: A total of 10205 cases of age group 1 month to 5 years presented to the paediatric OPD, out of which 193 children were diagnosed as congenital anomalies in 1 year. Males were found to be affected the most. The most common system involved was found to be the genitourinary system (36.78%). The second most common system involved was the gastrointestinal system (33.67%). The least common system involved was the musculoskeletal system. Conclusion: Congenital anomalies are a major cause of neonatal & infantile mortality & morbidity. Routine screening with a level II targeted scan for all the pregnant mothers should be mandatory. Adequate nutrition, parental education & Rubella vaccination of the mother can decrease the prevalence of congenital anomalies to some extend.